Effect of Science Laboratory Environment on Cognitive Development of Students - Muti-ur-Rehmaan Khan Niazi, Muhammad Aslam Asghar, Riasat Ali (PJDOL, 2023)
The purpose of the study was to find out the effects of existing physical environment of chemistry lab on cognitive learning of chemistry students in the rural and urban schools of Rawalpindi Division at secondary school level. The population of the study consisted of all science teachers and science students of all male and female schools inRawalpindi division. T